ISLAMIC LAW ANALYSIS OF MARRIAGE DISPENSATION FROM THE PERSPECTIVE OF MAQASID AL-SYARIAH - Ginanjar, Muhammad Sholeh; BW, Muh. Kurniawan; Pradana, Aditya Fajri Kurnia (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Every person's marriage is definitely inseparable from family life and life. The reasonable and healthy hopes or intentions of every young person or teenager in their growing years is one of the goals of marriage. In this case, the minimum age limit for marriage for women is equated with the minimum age limit for marriage for men, namely 19 (nineteen) years as stated in Law Number 16 of 2019. The aim of this research is to analyze Islamic law regarding marriage dispensations from the Maqasid Al-Shariah perspective. The type of research carried out in this research is normative juridical legal research, because the researcher used library materials as the main data to analyze cases, and the author did not conduct field research. The results of the research show that the judge's considerations regarding the protection of children's rights are certainly in line with the articles contained in the Marriage Law and are also in accordance with what is aimed at by maqāṣid al-sharīah, namely to maintain the benefit in which the judge positions the position of shari'ah as higher than Constitution.